Simulation of Soil Water and Heat Flow under Plastic Mulching and Different Ridge Patterns - Ruofan Li (MDPI AG, 2021)
The ridge–furrow mulching system with plastic film (RFMS) has been widely used in semi-arid areas in order to improve soil water and heat conditions, crop yields and water use efficiency. It is of practical significance to study the effect of mulching and ridge types on soil water and heat in order to optimize mulching measures and improve the effectiveness of the ridge and furrow system. To clarify the combined effect of soil water and heat beneath the system and the influence of ridge morphology on it, field experiments were conducted with three treatments, including conventional planting in bare land (CK), a ridge–furrow (wide ridge with 70 cm width and 10 cm height, narrow ridge with 40 cm width and 15 cm height) mulching system with complete plastic film (RFWN) and a ridge–furrow (equal ridge with 55 cm width and 15 cm height) mulching system with complete plastic film (RFE). An insufficient irrigation system was adopted and the two-dimensional numerical software HYDRUS-2D was used to simulate the soil water and heat flow under the experimental conditions. The model was calibrated and verified according to test data for the period of 2018 to 2019, which showed good agreement between the simulated and measured values. The simulation results revealed that the ground temperatures of RFWN and RFE were much higher than that of CK, and the average value of 0–25 cm during the growth period could increase by 2.29–4.61%. Compared with CK, RFWN and RFE reduced soil evaporation (84.71–93.73%) and field evapotranspiration (12.02–21.75%), while they increased root water uptake (25.87–40.98%) and T/ET (48.85–80.15%). Plastic film mulching and ridge morphologies affected the infiltration range and the direction of soil water movement, increased soil moisture when there was no rainfall or irrigation and reduced soil water and heat fluctuations, which was more conducive to crop growth, especially under the RFWN system. The simulation method proposed in this paper is an effective technique for calculating the soil water and heat dynamics under different ridge and furrow sections under the condition of film mulching, and it can be used for the optimal management of soil water and heat in this area.